Reliability and validity of the French adaptation of the Family Relationship Index–short form in patients' with chronic kidney disease. (January 2022) - Montalescot, Lucile; Speyer, Elodie; Legrand, Karine; Ayav, Carole; Combe, Christian; Stengel, Bénédicte; Untas, Aurélie
The Family Relationship Index (FRI) measures family cohesion, expressiveness and conflict. This study aimed to investigate its reliability and validity in patients with chronic kidney disease (CKD). Confirmatory factor analysis was performed on 1657 patients and on subgroups according to socio-demographics and medical variables. Two items with poor saturation were excluded. The indexes indicated an acceptable fit. Reliability was especially weak for expressiveness. Our results provide partial support for the use of the French-version of the FRI in patients with advanced CKD. The family relationship index should be used with caution, especially in certain subgroups and for the expressiveness subscale.